Increased TLR4 Expression Aggravates Sepsis by Promoting IFN-γ Expression in CD38−/− Mice - Qi Li; Chenyi Wu; Zhenlong Liu; Huiqing Zhang; Yuna Du; Yuxiang Liu; Kuangyu Song; Qiaofa Shi; Rong Li (Journal of Immunology Research)
Gram-negative bacterial sepsis accounts for up to 50% worldwide sepsis that causes hospital mortality. Acute kidney injury (AKI), a common complication of Gram-negative bacterial sepsis, is caused by Toll-like receptor 4 (TLR4) activation. Lipopolysaccharide (LPS) is an endotoxin in Gram-negative bacteria and is recognized specifically by TLR4, which initiates innate immune response. Also, TLR4 signaling pathway activation is essential in response to LPS infection. CD38 is one of the well-known regulators of innate immunity, whose dysregulation contributes to sepsis. Many studies have proven that an attenuated Gram-positive bacterium induces sepsis in a CD38-blocking model. However, the pathogenesis of Gram-negative bacteria-induced sepsis in a CD38−/− mouse model remains unclear. The aim of this study is to investigate whether kidney injury is still attenuated in a LPS-induced CD38−/− sepsis model and identify the potential mechanism. We assess the severity of kidney injury related to proinflammatory cytokine expressions (IFN-γ, TNF-α, IL-1β, and IL-6) in WT and CD38−/− mice. Our results showed more aggravated kidney damage in CD38−/− mice than in WT mice, accompanied with an increase of proinflammatory cytokine expression. In addition, compared with CD38−/−TLR4mut mice, we found an increase of TLR4 expression and mRNA expression of these cytokines in the kidney of CD38−/− mice, although only increased IFN-γ level was detected in the serum. Taken together, these results demonstrated that an increased TLR4 expression in CD38−/− mice could contribute to the aggravation of AKI through boosting of the production of IFN-γ.